The Impact of Input and Output Prices on Indonesian Coffee Production and Trade Performance - Fatkurrohim; Nuhfil Hanani; Syafrial (HABITAT, 2022)
Coffee is one of the most important agricultural plantation commodities in Indonesia, contributing 1.17 billion USD to the country's foreign exchange in 2017. Indonesia was also the world's fourth-largest coffee exporter from 2011 to 2017. However, the performance of coffee production and trade is very dynamic. In 2018, there was a significant drop in coffee exports by 40.23%, relegating Indonesia to sixth place even until 2020. Coffee production also fluctuates significantly, in contrast to the constantly rising coffee demand. This research aimed to figure out what factors influence Indonesian coffee production and trade performance. A simultaneous equation model using the 2SLS approach was employed as the methodology. The findings revealed that, in the production block, cocoa prices and interest rates had a significant influence (  10%) on the coffee land areas. In contrast, domestic coffee prices, rainfall, and trends significantly impacted coffee productivity. Meanwhile, in the trade block, domestic coffee prices and non-tariff dummy barriers significantly influence Indonesia's total coffee exports. As a result, it can be deduced that changes in the input prices (substitution commodity prices, interest rates, rainfall, and trend) have a better impact on coffee production, while the output prices (domestic coffee prices) on the coffee trade performance.